2013
DOI: 10.1242/jeb.072868
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic flexibility in migrating bats: seasonal variation in body composition, organ sizes and fatty acid profiles

Abstract: SUMMARYMany species of bats migrate long distances, but the physiological challenges of migration are poorly understood. We tested the hypothesis that migration is physiologically demanding for bats by examining migration-related phenotypic flexibility. Both bats and birds are endothermic, flying vertebrates; therefore, we predicted that migration would result in similar physiological tradeoffs. We compared hoary bats (Lasiurus cinereus) during spring migration and summer non-migratory periods, comparing our r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 77 publications
(104 reference statements)
1
47
1
Order By: Relevance
“…Migration-related changes were again complicated by sex differences: 22:6n-3 increased and 18:2n-6 decreased in migrant females, whereas the opposite occurred in males. Although total unsaturation did not change during migration, the double-bond index decreased in males and increased in females, and the n-6/n-3 ratio increased in males and decreased in females (McGuire et al, 2013a). Thus, no general pattern emerges regarding migrationrelated changes in the fatty acid composition of muscle membranes of free-living migratory birds and bats, except that changes in longchain n-3 PUFA appear to be offset by opposite changes in n-6 PUFA so that overall unsaturation remains stable (Guglielmo et al, 2002b;Maillet and Weber, 2006;McGuire et al, 2013a).…”
Section: Fatty Acid Composition Of Adipose Fat Stores and Flight Muscmentioning
confidence: 78%
See 4 more Smart Citations
“…Migration-related changes were again complicated by sex differences: 22:6n-3 increased and 18:2n-6 decreased in migrant females, whereas the opposite occurred in males. Although total unsaturation did not change during migration, the double-bond index decreased in males and increased in females, and the n-6/n-3 ratio increased in males and decreased in females (McGuire et al, 2013a). Thus, no general pattern emerges regarding migrationrelated changes in the fatty acid composition of muscle membranes of free-living migratory birds and bats, except that changes in longchain n-3 PUFA appear to be offset by opposite changes in n-6 PUFA so that overall unsaturation remains stable (Guglielmo et al, 2002b;Maillet and Weber, 2006;McGuire et al, 2013a).…”
Section: Fatty Acid Composition Of Adipose Fat Stores and Flight Muscmentioning
confidence: 78%
“…In studies of insectivorous bats sampled during autumn migration, fat loads were ∼25% of body mass whereas a frugivorous species had ∼12% body fat (Blem, 1980;Fleming and Eby, 2003). McGuire et al (2013a) found that female hoary bats were fatter during spring migration (16% of the total body mass) than during the summer (11%), but that males were lean in both seasons (11-12%). Fat stores of bats cannot be assessed visually owing to their thick fur; however, non-invasive QMR analysis has greatly increased our understanding of their fat storage (McGuire and Guglielmo, 2010).…”
Section: How Much Fat Is Stored?mentioning
confidence: 94%
See 3 more Smart Citations